2016
DOI: 10.5430/wje.v6n3p70
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Climate Change and Sustainable Development among Undergraduates from two Selected Universities in Oyo State, Nigeria

Abstract: This study investigated awareness of climate change and sustainable development among undergraduates in two universities: University of Ibadan, Ibadan and Ladoke Akintola University of Technology, Ogbomoso in Oyo State of Nigeria. This was aimed at increasing the knowledge of undergraduates on climate change and sustainable development.The study adopted a survey design. The population for the study consisted of 300 hundred undergraduates in University of Ibadan, Ibadan and Ladoke Akintola University of Technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 5 publications
0
15
0
2
Order By: Relevance
“…[20] (p. 25) Increasing peoples' awareness through education is an essential measure to drive active participation at all levels of the community in tackling climate change [8]. Agboola and Emmanuel [21], justify the need for awareness and enlightenment on climate change and sustainable development noting that awareness on climate change among the general public is pertinent whilst education is an essential component and catalyst for responding to global climate change. They examined climate change awareness among undergraduate students.…”
Section: Introductionmentioning
confidence: 99%
“…[20] (p. 25) Increasing peoples' awareness through education is an essential measure to drive active participation at all levels of the community in tackling climate change [8]. Agboola and Emmanuel [21], justify the need for awareness and enlightenment on climate change and sustainable development noting that awareness on climate change among the general public is pertinent whilst education is an essential component and catalyst for responding to global climate change. They examined climate change awareness among undergraduate students.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the results presented in this section could not be compared with findings of previous studies. One exception, however, is the study of Agboola and Emmanuel (2016), which reported lack of significant difference in the level of awareness of CC and sustainable development between the male and female students in their sample. However, these researchers did not provide an explanation of this finding.…”
Section: Differences Between the Sample Students In Knowledge Of Climate Changementioning
confidence: 89%
“…Corollary to this, Crowley (2000) and Frigg, Thompson, and Wernd (2015) emphasized the finding that the temperature increase in the late 20 th century was caused primarily by GHG forcing and that, accordingly, our trust in that the GHGs explain the global warming is quite high. These gases mainly include carbon dioxide (CO 2 ), methane (CH 4 ), ammonia (NH 3 ), nitrous oxide (N 2 O), chlorofluorocarbons (CFCs), and sulfur hexafluoride (SF 6 ) (Agboola & Emmanuel, 2016;Odjugo, 2010). Carbon dioxide is the particular GHG emitted at the highest quantities, followed by CH 4 , the CFCs, and N 2 O (Odjugo, 2010).…”
Section: Causes Of Climate Changementioning
confidence: 99%
See 2 more Smart Citations